Design, validation, and reliability of the Bangor rugby assessment tool for evaluating technical and tactical skills in rugby union development pathways - Lowe, George C.; Owen, Julian A.; Gottwald, Victoria M.; Jones, Eleri S. (Frontiers in Sports and Active Living, 2025)
IntroductionPlayer profiling is fundamental to effective talent identification and development strategies. However, whilst anthropometric and physiological profiling is customary practice, effective evaluation of technical and tactical skills in team sports has arguable been overlooked, largely due to a lack of suitable measurement tools. Therefore, the aim of the present study was to design, validate, and test the reliability of a novel observational instrument for assessing technical and tactical skills in rugby union.MethodsThe Bangor Rugby Assessment Tool (BRAT) was developed via the following three stages: (1) completion of a targeted literature search and expert focus group to inform initial item content; (2) Bayesian structural equation modelling (BSEM) to examine instrument factor structure; and (3) establishment of instrument reliability using intraclass correlation coefficients (ICC).ResultsResults demonstrate excellent model fit (PPP = 0.511) and strong validity for both the technical and tactical factors. ICC values ranged from moderate to excellent, demonstrating good reliability (0.79).DiscussionThe assessment tool offers a valid and reliable measure of technical and tactical aptitude within rugby union, whilst maintaining the requisite practical utility valued by practitioners.